1988
DOI: 10.1111/j.1432-1033.1988.tb14124.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and isolation of glucose dehydrogenase genes of Bacillus megaterium M1286 and their expression in Escherichia coli

Abstract: A gene encoding glucose dehydrogenase of Bacillus megaterium M1286 was isolated from a λ‐EMBL3 phage library. It is transcribed and translated in cells of the heterologous organism Escherichia coli by own control regions. The gene is located on a 1126‐bp HindIII fragment. Its nucleotide sequence contains 220 bp in the 5′ non‐coding region, 783 bp in the coding region and 123 bp in the 3′ non‐coding region. The amino acid sequence, as deduced from the coding region, consists of 261 amino acids and is different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…4). GNO from G. oxydans displayed the typical pattern of six strictly conserved residues which has been found in all group II alcohol dehydrogenases that have been sequenced, i.e., glucose dehydrogenase from Bacillus megaterium (18), alcohol dehydrogenase from Drosophila melanogaster (45), ribitol dehydrogenase from Klebsiella aerogenes (13), 3-␤-hydroxysteroid dehydrogenase from Pseudomonas testosteroni (51), cis-benzene glycol dehydrogenase from Pseudomonas putida (19), and acetoacetyl-coenzyme A reductase from Alcaligenes eutrophus (29). The glycine residues at positions 18, 22, and 24 correspond to the spacing expected for pyridine nucleotide binding sites, as shown for other dehydrogenases (20,33,49).…”
Section: Resultsmentioning
confidence: 85%
“…4). GNO from G. oxydans displayed the typical pattern of six strictly conserved residues which has been found in all group II alcohol dehydrogenases that have been sequenced, i.e., glucose dehydrogenase from Bacillus megaterium (18), alcohol dehydrogenase from Drosophila melanogaster (45), ribitol dehydrogenase from Klebsiella aerogenes (13), 3-␤-hydroxysteroid dehydrogenase from Pseudomonas testosteroni (51), cis-benzene glycol dehydrogenase from Pseudomonas putida (19), and acetoacetyl-coenzyme A reductase from Alcaligenes eutrophus (29). The glycine residues at positions 18, 22, and 24 correspond to the spacing expected for pyridine nucleotide binding sites, as shown for other dehydrogenases (20,33,49).…”
Section: Resultsmentioning
confidence: 85%
“…9) revealed that all of these residues except tyrosine were located at the N-terminal ends of putative p-pleated sheets, the latter being located at the carboxyl end of a ,B sheet. (20), ribitol dehydrogenase from Klebsiella aerogenes (13), and alcohol dehydrogenase from D. melanogaster (44). Multiple sequence alignment and gapping was done by using the GCG Gap, Lineup, and Pretty programs, and a consensus sequence was generated.…”
Section: Resultsmentioning
confidence: 99%
“…The ORF4 product is similar to a group of oxidoreductases ( Fig. 3), including the protochlorophyllide reductase (Pcr) of barley (33), the glucose dehydrogenase of Bacillus megateium (19), the ribitol dehydrogenase of Kgebsiella aerogenes (28), and the NodG protein of Rhizobium meliloti (which is homologous to ,B-ketoacyl reductase [34]). The similarity among these oxidoreductases was stronger at the N termini.…”
Section: Methodsmentioning
confidence: 99%